Human work interaction design : designing engaging automation : 5th IFIP 13.6 Working Conference, HWID 2018, Espoo, Finland, August 20-21, 2018, Revised selected papers /: designing engaging automation : 5th IFIP 13.6 Working Conference, HWID 2018, Espoo, Finland, August 20-21, 2018, Revised selected papers. (2019) - Unknown
No abstract available